2021
DOI: 10.48550/arxiv.2105.02237
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Probabilistic model for dynamic galaxy decomposition

Yesukhei Jagvaral,
Duncan Campbell,
Rachel Mandelbaum
et al.

Abstract: In the era of precision cosmology and ever-improving cosmological simulations, a better understanding of different galaxy components such as bulges and discs will give us new insight into galactic formation and evolution. Based on the fact that the stellar populations of the constituent components of galaxies differ by their dynamical properties, we develop two simple models for galaxy decomposition using the IllustrisTNG cosmological hydrodynamical simulation. The first model uses a single dynamical parameter… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 65 publications
2
4
0
Order By: Relevance
“…We employ a minimum stellar mass threshold of log 10 (𝑀 * /𝑀 ) = 10 for all galaxies, using their stellar mass from the SUBFIND catalog. A previous study (Jagvaral et al 2021) motivates the mass cut on the shape sample, where we concluded that the disc fractions from TNG100-1 agree well with observational values down to log 10 (𝑀 * /𝑀 ) = 10, below which we believe the resolution of the simulation may be affecting the results. Also, we have checked that using a lower mass on the density tracers, to include more galaxies, did not change our 𝐴 𝐼 amplitudes.…”
Section: Sample Selectionsupporting
confidence: 78%
See 3 more Smart Citations
“…We employ a minimum stellar mass threshold of log 10 (𝑀 * /𝑀 ) = 10 for all galaxies, using their stellar mass from the SUBFIND catalog. A previous study (Jagvaral et al 2021) motivates the mass cut on the shape sample, where we concluded that the disc fractions from TNG100-1 agree well with observational values down to log 10 (𝑀 * /𝑀 ) = 10, below which we believe the resolution of the simulation may be affecting the results. Also, we have checked that using a lower mass on the density tracers, to include more galaxies, did not change our 𝐴 𝐼 amplitudes.…”
Section: Sample Selectionsupporting
confidence: 78%
“…For the Red sample we present both the mass-controlled and the full sample; however the Blue sample was not mass controlled because of its very narrow mass range. Here, we should note that the simulation produces a slightly higher number of red disc galaxies compared to observations, which complicates the interpretation of these results (Nelson et al 2018;Jagvaral et al 2021). The Blue sample has an IA signal that is consistent with zero, similar to previous studies in real data such as Johnston et al (2019); Mandelbaum et al (2011).…”
Section: Alignment Measurements From Two-point Functionssupporting
confidence: 60%
See 2 more Smart Citations
“…First off it is simpler and more direct to compare observation with simulations or semianalytic models. Similar to observations it is non-trivial to separate galaxies into different components in simulations (Obreja et al 2018;Jagvaral et al 2021) and the methods used are different then in observations. In the MGE framework it is simple to compare mass or light profiles or focus on specific parts of the galaxy that are of interest like the central regions or outskirts.…”
Section: Discussion and Summarymentioning
confidence: 99%